The influence of Sc solute partitioning on the microalloying effect and mechanical properties of Al-Cu alloys with minor Sc addition. (15th October 2016) - Yang, C.; Zhang, P.; Shao, D.; Wang, R.H.; Cao, L.F.; Zhang, J.Y.; Liu, G.; Chen, B.A.; Sun, J.
Abstract: A transmission electron microscope and an atom probe tomography were used to quantitatively characterize the microstructural evolution of Al-XCu alloys (X = 1.0, 1.5, and 2.5 wt%) with 0.3 wt% Sc addition. A dual solute alloying/microalloying effect on the microstructural evolution was demonstrated. On the one hand, the nucleation and coarsening of Al3 Sc dispersoids displayed a Cu alloying effect . By increasing the Cu content, both the Al3 Sc disperoid size and the volume fraction decreased after solution treatment. On the other hand, the precipitation of θ′ -Al2 Cu strengthening particles during aging treatment was promoted by Sc segregation at the θ′ /matrix interfaces, showing a notable Sc microalloying effect . The strongest interfacial Sc segregation was generated in the Al-2.5 wt%Cu-Sc alloy, resulting in the most promoted θ′ precipitation. The Sc partitioning between Al3 Sc dispersoids and Sc segregation at the θ′ /matrix interfaces, tailored by the Cu content, impacted the mechanical properties and deformation behavior at both room temperature and high temperature. The Al-2.5 wt%Cu-Sc alloy had a room temperature yield strength of approximately 2.2 times that in its Sc-free counterpart and approximately 1.8 times that in the Al-1.5 wt%Cu-Sc alloy, which is rationalized by strengthening models. In addition, the improvement in the high-temperature mechanical properties after Sc addition was discussed in terms of the Sc segregation-induced high coarsening resistance of θ′ precipitates. Graphical abstract: